Ketamine in palliative care: an updated systematic review - Dowierciał, Kinga; Wziątek, Joanna; Kowalik, Piotr; Krzyżanowska, Daria; Fatyga, Patrycja; Fatyga, Wiktoria; Pabis, Gabriela; Bętkowska, Paula; Koziołek, Iwona; Strzelczyk, Magdalena (Quality in Sport, 2025)
Introduction Ketamine is a well-known anesthetic and analgesic agent which primarily works through N-methyl-D-aspartate (NMDA) receptor antagonism, offering powerful analgesic effects that is particularly useful in opioid-refractory pain. Beyond pain control, it garnered significant attention in depression and anxiety research, which are some of the most frequent and serious symptoms experienced by patients in need of palliative care. This article provides an overview of Ketamine therapeutic applications in treatment of depression, anxiety, physical pain, opioid tolerance and opioid-induced hyperalgesia (OIH), drawing on research from PubMed published between 2020 and 2025. Aim of study This review aims to present the current state of knowledge regarding Ketamine, focusing on its pharmacological properties, clinical applications, and potential role in palliative care. Material and methods The review was based on research of articles published from 2020 to 2025 on the PubMed database. Keywords used in research were among others: Ketamine, palliative care, pain, neuropathic pain, depression. Current state of knowledge Ketamine plays important role in anesthesiology and it shows a lot of potential in psychiatry. Multifactoral effects result from complex mechanism of action. Evidence suggests Ketamine can be effective in managing refractory pain (enabling lower doses of opioids even in severe pain), depression and anxiety disorders, opioid tolerance and OIH, positioning ketamine as a promising agent for palliative care. Summary (conclusions) Ketamine's advantages such as its rapid onset, wide range applications, favorable safety profile at subanesthetic doses and many routes of administration make it a valuable tool in the end-of-life care. However long term studies are crucial for identifying both benefits and possible risks.